أثر استخدام أسلوبي التعلم التعاوني والتعلم التنافسي الجماعي في تعلم مهارة التصويب من القفز عاليا بكرة اليد - شاهۆیی, ابراهيم محمد مصطفى (Sulaimani Journal for Humanities, 2022)
The aim of the research is to discover: Preparing two educational curricula in cooperative learning and group competitive learning methods in learning the skill of shooting from high jumping in handball for second stage students in the faculty of physical education / Koya University. - Detecting the effect of the cooperative learning and group competition learning styles in learning the skill of shooting from high jumping with handball. - Identifying the differences between the two methods in the post-test of the performance of the shooting skill from jumping high with handball. The researcher used the experimental method for its suitability to the nature of the research, and the research sample was the students of the second stage in the two faculty of physical education - Koya University, which numbered (24) students and by (12) students for each group. Team competition, and the research tools were represented in the specific skill test in handball (shooting from high jump), After completing the application of the program, the post-test was conducted, and after data collection, unloading and processing by appropriate statistical means, the researcher reached a set of conclusions: - Teaching in a cooperative learning style was influential in learning the skill of shooting from jumping high, as the results showed that there were statistically significant differences in the tribal and remote measurements, in favor of the dimensional measurements. - Teaching in the group competition method was influential in learning the skill of shooting from jumping high, as the results showed that there were statistically significant differences in the tribal and remote measurements, in favor of the dimensional measurements. - The use of the collective competition method greatly helped in reducing the effort expended in the process of correcting errors and providing feedback on the type of error by the learners. In light of the conclusions recommended by the researcher. - Using cooperative learning and group competition methods in teaching basic handball skills because of their significant impact on learning. - Training teachers to use modern methods in the learning process, because the teacher's knowledge of the method makes it easier for him to teach.
Keywords: educational curriculum; cooperative learning method; team competition method; high jump shooting skill; handball